Xây dựng bài tập mở rộng vốn từ hỗ trợ học sinh lớp 1 có khó khăn về đọc /Nguyễn Thị Ly Kha. - Nguyễn, Thị Ly Kha.
This article presents an experimental research on building vocabulary expansion exercises to support first grade dyslexic students in Ho Chi Minh City. The results of the research show that these exercises have strong positive effects on reading capacity of dyslexic students. These exercises should be applied together with phonemic awareness, phonological awareness, spelling awareness and reading fluency and comprehension exercises.